Evaluating the effect of lactic acid bacteria fermentation on quality, aroma, and metabolites of chickpea milk - Zhang, Panling; Tang, Fengxian; Cai, Wenchao; Zhao, Xinxin; Shan, Chunhui (Frontiers in Nutrition, 2022)
This study evaluated the impact of Lactobacillus plantarum fermentation on the physicochemical parameters, vitamins, organic acids, aroma substances, and metabolites of chickpea soymilk. The lactic acid bacteria (LAB) fermentation improved the color, antioxidant properties, total phenolic content, total flavonoid content, lactic acid content, and vitamin B6 content of raw juice. In total, 77 aroma substances were identified in chickpea soymilk by HS-SPME-GC-MS (Headspace solid-phase microextraction with gas chromatography/mass spectrometry); 43 of the 77 aroma substances increased after the LAB fermentation with a significant decrease in beany flavor content (p < 0.05), improving the flavor of the milk product. Also, a total of 218 metabolites were determined in soymilk using non-targeted metabolomics techniques, including 51 differentially metabolites (28 up-regulated and 23 down-regulated; p < 0.05). These metabolites participated in multiple metabolic pathways during the LAB fermentation, ultimately improving the functional and antioxidant properties of fermented soymilk. Overall, LAB fermentation can improve the flavor, nutritional, and functional value of chickpea soymilk accelerating its consumer acceptance and development as an animal milk alternative.